Analisis Faktor Produksi Terhadap Produksi Semangka (Citrullus Vulgaris, Scard) di Kecamatan Tampan Kota Pekanbaru - Reni Ismawati; Cepriadi '; Roza Yulida (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This study aims to identifying the influence of production factor to mustard production and to analyze the allocation efficiency of the production factor watermelon farm. The estimated result with Cobb-Douglass production function and Efficiency analysis. The results showed simultaneously all the independen variables (X) obvious effect the dependent variable (Y). Partial fertilizer ZA, SP-36 and Gandasil significantly effect the production of watermelon in the District Tampan City Pekanbaru, sig value 0,000 < 0,01 in level 95%. The NPM/Px value for organic fertilizer, ZA, SP-36, antracol, tupermin, dupont, seprint,EM-4 and labour usage is ≥ 1, it means the usage both of that factors can be increased. The value of NPM/Px for seed, fertilizer NPK and KCL is not important to reach economic efficiency condition and get the maximum benefit Keyword :Efficiency, Production Factor, District Tampan, Watermelon, Farm